Pengaruh Metode Pemanasan Terhadap Karakteristik Mutu Teh BerasMerah Jatiluwih - IPutu Gde Budisanjaya; Luh Putu Wrasiati; IMadeAnom Sutrisna Wijaya (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2015)
Red rice tea is a product that became popular in the area of agro Jatiluwih, Penebel District,Tabanan, Bali Province. Tourists who visit this region are usually offered warm drink tea red riceand red rice tea also bought in packs. However, the quality of red rice tea produced by KWTKuntum Sari in the agrotourism Jatiluwih is not yet stable. Flavor, color and aroma are changingevery times of production. Besides, the appearance of a product that is less attractive because it ispacked with roughing plastic and not labeled so that the product information can not be knownthrough the packaging. These unstable products results in poor marketing of this tea out of agrotourismarea. For that reason research on improving the quality of red rice tea which includes theimprovement of production and packaging process is necessary to be done. The purpose of thisstudy was to determine the influence of the production method (roasting and oven drying) anddetermine the production process that produces good quality of red rice tea. This research wasconducted in the village of Wangaya Betan, Penebel District, Tabanan and in the Food AnalysisLaboratory, Faculty of Agricultural Technology, University of Udayana. The results showed thatthere were differences in the chemical characteristics of red rice tea produced by oven drier androaster. Red rice tea is produced by means of oven contains higher anthocyanins, total phenols,tannins, and antioxidant capacity compared with roasted red rice tea, but has a lower watercontent compared with roasted red rice tea. While the macro chemical composition such asproteins, fats, carbohydrates and water are relatively similar between red rice teas by roasting andovendrying method.